Sopimukset vastuullisuuden edistäjinä ja mutkistajina yritysten toimitusketjuissa – esimerkkinä mallilausekkeiden ymmärrettävyys - Oksanen, Henrik; Ketola, Anne; Haapio, Helena; Hurmerinta-Haanpää, Anna (VAKKI communication research association, 2025)
Corporate sustainability has become ever more important in today’s ecological crisis. Thus, regulators around the world have started to push companies towards more sustainable business practices. The contracts that companies use in their business operations are central in implementing environmental and social responsibility. Following recent regulatory developments, such as the EU corporate sustainability due diligence directive (the EU CSDDD), several sets of model contract clauses have been created for companies to use to improve the human rights and environmental performance of their contracts in supply chains. These model clauses are an important step towards sustainable value chains. Our article aims to demonstrate, however, that the language used in these clauses is so complex that it compromises their actionability. We shed light on these potential comprehension problems with examples from the European Model Clauses for Responsible and Sustainable Supply Chains (EMCs), developed by an independent group of mainly European legal practitioners and scholars. We analyze the model clauses both lexically and syntactically in order to illustrate how the various lexical and syntactic features form different kinds of potential comprehension problems in the model contract clauses, thus hampering their function of facilitating change towards more sustainable contracting. In addition to illustrating possible problems for comprehension, we suggest ways to improve the comprehensibility of the EMCs.
Keywords: sopimuskieli; sustainabilitese; vastuullisuus; ymmärrettävyys; fi=Talousoikeus|en=Business Law|